Editor's Choice – Early and Late Outcomes after Transcarotid Revascularisation for Internal Carotid Artery Stenosis: A Systematic Review and Meta-Analysis. (May 2021) - Galyfos, George C.; Tsoutsas, Ioannis; Konstantopoulos, Theofanis; Galanopoulos, Georgios; Sigala, Frangiska; Filis, Konstantinos; Papavassiliou, Vassilios
Abstract : Objective: Transcarotid/transcervical revascularisation (TCAR) is an alternative to carotid endarterectomy (CEA) and transfemoral carotid stenting (tfCAS). This review aimed to evaluate pooled data on patients undergoing TCAR. Data sources: Medline, Embase, Scopus, and Cochrane Library databases were used. Review methods: This systematic review was conducted under Systematic Reviews and Meta-Analysis guidelines. Eligible studies (published online up to September 2020) reported 30 day mortality and stroke/transient ischaemic attack (TIA) rates in patients undergoing TCAR. Data were pooled in a random effects model and weight of effect for each study was also reported. Quality of studies was evaluated according to Newcastle – Ottawa scale. Results: Eighteen studies (three low, seven medium, and eight high quality) included 4 852 patients (4 867 TCAR procedures). The pooled 30 day mortality rate was 0.7% ( n = 32) (95% confidence interval [CI] 0.5 – 1.0), 30 day stroke rate 1.4% ( n = 62) (95% CI 1.0 – 1.7), and 30 day stroke/TIA rate 2.0% ( n = 92) (95% CI 1.4 – 2.7). Pooled technical success was 97.6% (95% CI 95.9 – 98.8). The cranial nerve injury rate was 1.2% (95% CI 0.7 – 1.9) ( n = 14; data from 10 studies) while the early myocardial infarction (MI) rate was 0.4% (95% CI 0.2 – 0.6) ( n = 16; data from 17 studies). The haematoma/bleeding rate was 3.4% (95% CI 1.7 – 5.8) ( n = 135; data from 10 studies), with one third of these cases needing drainage or intervention. Within a follow up of 3 – 40 months the restenosis rate was 4% (95% CI 0.1 – 13.1) (data from nine studies; n = 64/530 patients) and death/stroke rate 4.5% (95% CI 1.8 – 8.4) (data from five studies; n = 184/3 742 patients). Symptomatic patients had a higher risk of early stroke/TIA than asymptomatic patients (2.5% vs. 1.2%; odds ratio 1.99; 95% CI 1.01 – 3.92); p = .046; data from eight studies). Conclusion: TCAR is associated with promising early and late outcomes, with symptomatic patients having a higher risk of early cerebrovascular events. More prospective comparative studies are needed in order to verify TCAR as an established alternative treatment technique.